Passenger Train Accidents and the Accountability of PT Kereta Api Indonesia: A Critical Study on the Effectiveness of Law No. 23 of 2007 - Pratiwi, Aurel Dwi Elza; Mulyanti, Asti Sri (Universitas Semarang, 2025)
Rail transportation has a crucial role in supporting community mobility and the distribution of goods in Indonesia. However, train accident cases still occur frequently with alarming numbers. Data from the National Transportation Safety Committee (KNKT) recorded 103 accident incidents between 2007 and 2023, with a frequency of 1 to 13 cases per year. Many of these accidents result in thousands of fatalities and compensation claims each year, underscoring the need for effective legal protections for passengers as consumers of public transport. This study aims to examine the legal responsibility of PT Kereta Api Indonesia (Persero) based on Law No. 23 of 2007, especially the implementation of compensation for accident victims. The method used was normative juridical with the support of secondary data and short interviews. The results show that although the regulation has established the principle of absolute accountability for PT KAI, its implementation still faces serious obstacles, such as complicated claim procedures, a lack of socialization of passenger rights, low legal literacy of victims, and a lack of data integration between institutions such as PT KAI, hospitals, police, and Jasa Raharja. As a result, many victims receive only basic compensation without full compensation. This research emphasizes the need for system reform through the digitization of claims, strengthening socialization, and integration of cross-institutional databases. Academically, the study highlights the gap between regulation and practice and provides concrete recommendations to improve claims management and consumer protection of public transport.